Media Dissemination â€œThe Threat of Tsunami Unleashed from the Eruption of Mount Anak Krakatauâ€ Through Documentary Movie - Rezaldi, Muhamad Yudhi; Soeprihantoro, Wahjoe (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2015)
The Eastern side of the Sunda Strait coastal line is an area which faces directly towards the source of the disaster. Mount Krakatauâ€™s explosion causes major eruptions and destructive tsunami waves back in 1883, causing severe damages to the area and a death-count reaching 30,000 people. Learning from past, it is important to convey the understanding of natural hazards to the public. Spreading knowledge of the threat needs to be done by using methods that can easily be accepted, understood and implemented by any kind of communities. This preliminary research compels that the general population does not have sufficient understanding on this natural disaster. They are also oblivious to what procedure should be taken when such a tragedy occur. The research also illustrates that the audio-visual media is the most appropriate and favored method of gaining knowledge by the community. The media is constituted of multiple segments of 3D animations, digital computer animations, and short field-filmed clips, which are then assembled into one single documentary presenting both a virtual-reconstruction of the event whilst giving a variety of information concerning the subject. The content of the documentary will provide information about the Krakatau tsunami, the current condition of Mount Anak Krakatau, the signs leading to a volcanic eruption and a tsunami, and the necessary steps that they will have to follow in response to such threat. This documentary movie will hopefully become an educational tool to expand people's knowledge and awareness at the event of an eruption and a tsunami.